2017
DOI: 10.1016/j.vetmic.2016.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel recombinant virulent avian infectious bronchitis virus

Abstract: The emergence of new infectious bronchitis virus (IBV) variants is often disastrous in the poultry industry. In this study, an IBV, CK/CH/2010/JT-1, was isolated from an H120- and 4/91-IBV-vaccinated flock in China. Antisera against vaccine strains H120 and 4/91 could not provide effective protection against CK/CH/2010/JT-1 in virus neutralization assays. CK/CH/2010/JT-1 could cause 43.75% mortality with respiratory and severe renal lesions in inoculated chickens. Phylogenetic analysis of the S1 gene showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
2
27
0
2
Order By: Relevance
“…It has been reported that the side effects of the 4/91 vaccine might provide the basis for recombination with other strains. This phenomenon has been shown by several studies which have traced the emergence of many novel IBV strains to recombination events between the 4/91 vaccine and field strains (Feng et al, 2018;Han et al, 2017;Jiang et al, 2017Jiang et al, , 2018Liu et al, 2013;Mo et al, 2013;Ovchinnikova et al, 2011;Zhang et al, 2015Zhang et al, , 2016Zhou et al, 2017) in cases where the 4/91 vaccine strain could not provide effective protection against the field strains , leading to coinfection of the vaccine and field strains in the same chickens and ultimately resulting in recombination. In this study, we performed complete genome sequence analysis of strains I0718/17, I0722/17, I0724/17, and I0737/17 and confirmed the occurrence of recombination events at the 5′ ends of the S1 gene between a 4/91-like virus (GI-13 lineage) and a YX10-like virus (GI-19) (Xu et al, 2018), which contributed to the emergence of the IBV strains.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that the side effects of the 4/91 vaccine might provide the basis for recombination with other strains. This phenomenon has been shown by several studies which have traced the emergence of many novel IBV strains to recombination events between the 4/91 vaccine and field strains (Feng et al, 2018;Han et al, 2017;Jiang et al, 2017Jiang et al, , 2018Liu et al, 2013;Mo et al, 2013;Ovchinnikova et al, 2011;Zhang et al, 2015Zhang et al, , 2016Zhou et al, 2017) in cases where the 4/91 vaccine strain could not provide effective protection against the field strains , leading to coinfection of the vaccine and field strains in the same chickens and ultimately resulting in recombination. In this study, we performed complete genome sequence analysis of strains I0718/17, I0722/17, I0724/17, and I0737/17 and confirmed the occurrence of recombination events at the 5′ ends of the S1 gene between a 4/91-like virus (GI-13 lineage) and a YX10-like virus (GI-19) (Xu et al, 2018), which contributed to the emergence of the IBV strains.…”
Section: Discussionmentioning
confidence: 87%
“…Although IBV (and other coronaviruses) has a 3′ to 5′ exoribonuclease (exon) domain in Nsp 14 that is involved in proofreading and repair (132), the average rate of synonymous mutation is still high at approximately 1.2 × 10 -3 substitutions/ site/year (87,89). Recombination has been reported in many coronaviruses including IBV (88,167,186). Since the replicase gene was shown to be a determinant of pathogenicity (8), recombination in the 1a/1ab genes associated with the RDRP can affect pathogenicity.…”
Section: Strains Of Ibv and Viral Evolutionmentioning
confidence: 99%
“…In China, several epidemiological IB surveys have already been conducted and have shown that a variety of IBV genotypes and variants Mo et al, 2013;Zhao et al, 2013;Liu et al, 2014;Zhou et al, 2014;Chen et al, 2015;Xu et al, 2016;Zhang et al, 2015;Leghari et al, 2016;Chen et al, 2017;Zhao et al, 2017;Zhou et al, 2017) are circulating and cocirculating. This shows that the Chinese IBV situation is complex and variable, and causes serious economic losses in the Chinese poultry industry.…”
Section: Introductionmentioning
confidence: 99%